Model ages of fracture fillings and mineralogical and geochemical evidence for water-rock interaction in fractures in granite: The Melechov Massif, Czech Republic. (August 2018) - Procházka, Václav; Zachariáš, Jiří; Strnad, Ladislav
Abstract: The mineral, chemical and Pb-isotope composition were investigated in the host granite and low-temperature open-fracture fillings from the 100 m deep borehole PDM-1 located in the Melechov Massif of the Moldanubian Batholith. The fillings are dominated by limonite and clay-mineral (illite, kaolinite, montmorillonite, nontronite, chlorite) mixtures, accompanied by minor amounts of residual minerals from the parent rock (quartz, feldspars, zircon, monazite). Chemically contrasting fracture assemblages occur mainly at lesser depths (<55 m), where a high content of Fe-oxides and hydroxides locally with Mn-oxides is common. High Fe is correlated with a very high content of U, P, and V, whereas Mn is accompanied by Li, Co, Ni, Zn and Ba. Enrichment in mechanically transported primary accessory minerals and their gravity sorting in the flow of paleogroundwater is the most probable explanation for high REE, Y, Zr, Hf and Th in some samples. The fracture fillings mostly have higher U/Pb and 206 Pb/ 207 Pb ratios than the parent rock, which enables them to be dated by a one-stage model. The model ages indicate major U-Pb redistribution event around 130 Ma which is assumed to represent the main episode of formation of clay-rich fillings, and minor events at 280 Ma and in the Tertiary, whereas the Quaternary processes were of minimal importance. Formation of fractures in the fresh granite, however, occurred shortly after its solidification (ca. 300-320 Ma). Highlights: The clayey open-fracture fillings are derived from the parent ∼310 Ma old Kouty granite. They are mostly enriched in Fe, Mn and trace elements like Co, Cu, U, Pb. In some fillings, detrital accessory minerals were concentrated by groundwater flow. The U-Th-Pb isotope systems indicate major U-Pb redistribution event at 130-140 Ma. This event may correspond to supergene oxidation of sulfides and uraninite.